Real-time passive acoustic monitoring of HIFU-induced tissue damage. - Nandlall, S; Jackson, E; Coussios, C (2011)
Thermal ablation by high-intensity focused ultrasound (HIFU) shows great promise as a noninvasive cancer therapy. This work proposes a novel method of real-time HIFU treatment monitoring that uses the passively monitored acoustic signal emanating from the focus during HIFU exposure. We performed 212 exposures in seven freshly excised ox livers using 1.067-MHz HIFU at a 95% duty cycle for a range of insonation durations and acoustic intensities. Acoustic emissions were recorded using a 15-MHz passive detector aligned confocally and coaxially with the HIFU transducer. Lesion presence and size were ascertained by slicing the tissue in the transverse and axial focal planes post exposure. Our results demonstrate that successful formation of HIFU lesions in ex vivo ox liver is highly correlated with the presence of pronounced dips in the magnitude of the received signal at integer harmonics of the insonation frequency. A detector based on this observation predicted lesioning with >80% accuracy in regimes that were very likely to create lesions (≥60 J of energy) and had an error rate of <6% for exposures that were too short to cause lesioning (≤1 s long). The overall sensitivity and specificity of the detector were 75.6% and 74.2%, respectively. The proposed detector could therefore provide a low-cost means of effectively monitoring clinical HIFU treatments passively and in real time.